27.6k views
0 votes
Solve the given system 3y=-4x-22
y=-5x-11

User Gottox
by
5.3k points

1 Answer

7 votes

Answer:

(-1, -6)

Explanation:

3y=-4x-22

y=-5x-11

(y=-5x-11)*3 ==> make this equation equal to 3y, so you can eliminate y

3y = -15x - 33

Solve for x:

-15x - 33 = -4x - 22 ==> since both expression equal 3y

-15x + 15x - 33 = -4x + 15x - 22 ==> add 15x on both side to remove -x

-33 = 11x - 22

-33 + 22 = 11x - 22 + 22 ==> add 22 on both sides to isolate x

-11 = 11x ==> simplify

x = -1

Solve for y:

y=-5(-1)-11 ==> plugin -1 for x

y=5-11

y = -6

x = -1, y=-6 ==> (-1, -6)

User Shika
by
4.5k points